Mediating function of heart failure in the causal relationship between diastolic blood pressure and hypertensive renal disease with renal failure: a mediated Mendelian randomization study† - Pang Lei; Ding Zi-Jun; Chai Hong-Qiang; Li Fei; Wu Ming; Shuang Wei-Bing (Sciendo, 2024)
To study the causality relationship between diastolic blood pressure (DBP) and hypertensive renal disease with renal failure (HRDRF) and the mediating role of heart failure (HF) in the causality relationship by network Mendelian randomization (MR).